Estudo da compactação de resíduos lignocelulósicos para utilização como combustível sólido - Chrisostomo, Walbert (2011)
The production of energy from the combustion of lignocellulosic materials is an interesting way to waste recovery. Two main factors hampering the use of these residues as fuel are the low density and the high moisture content. Compression of lignocellulosic residues can be a way of producing solid fuel of better quality. The aim of this study was to evaluate the quality of solid fuels (briquettes) produced from the compaction of waste generated in lignocellulosic agroindustrial processes. The materials used in this study were: sugar cane bagasse, sawdust of Eucalyptus sp and sawdust of Pinus sp. The residues were compressed under the same conditions of particle size (particle size ranging from 20 to 40 mesh) and moisture content (10% dry basis). The compression was performed in a hydraulic press, without heating. The compaction pressure used was 1250 kgf.cm-2 and the time of application of the maximum load was 15 seconds. The production of briquettes was possible with the three types of materials used. The briquettes produced had densities ranging between 840 and 872 kg.m-3. This represented a volume decrease of 12.2 times for the sugar cane bagasse, 6.01 times for the eucalyptus and 5.28 times for the pine. The longitudinal expansion of the briquettes was 9.44% for the eucalyptus, 9.61% for the sugarcane and 10.76% for the pine. The results of diametral compression test were 1.01 MPa (eucalyptus), 0.61 MPa (cane) and 0.45 MPa (pine). The higher heating values (HHV) found were 4675 kcal.kg-1 (pine), 4436 kcal.kg-1 (eucalyptus) and 4138 kcal.kg-1 (cane). The results showed that all the materials tested can be used in the production of briquettes and the production of briquettes was possible by compression without heating. The compacting process improved the quality of solid biofuel.